The Active plus protocol: systematic development of two theory- and evidence-based tailored physical activity interventions for the over-fifties - de Vries Hein; Kok Gerjo; van Stralen Maartje M; Mudde Aart N; Bolman Catherine; Lechner Lilian (BMC, 2008)
Abstract Background Limited data are available on the development, implementation and evaluation processes of physical activity promotion programmes among older adults. More integrative insights into interventions describing the planned systematic development, implementation and evaluation are needed. Methods and design The purpose of this study is to give an integrative insight into the development of the Active plus programme applying the six-step Intervention Mapping protocol. The Active plus programme consisted of two theory- and evidence-based tailored physical activity promotion interventions, both comprising three tailored letters delivered over four months and aimed at raising awareness of insufficient physical activity, and stimulating physical activity initiation and maintenance among the over-fifties. The first intervention, the basic tailored intervention, provided tailored letters that intervened on the psychosocial determinants of physical activity. The second intervention, the intervention plus, provided the same tailored information but additionally provided tailored information about physical activity opportunities in the specific environment in which the older adults lived. This environment-based component also provided access to a forum and e-buddy system on a website. A plan for implementation and evaluation is also described. Discussion The planned development of the Active plus programme resulted in two theory- and evidence-based tailored physical activity interventions targeted at the over-fifties. Trial Registration Dutch Trial Register NTR 920